PELAKSANAAN PENGAWASAN OLEH KEPALA DESA DALAM UPAYA MENINGKATKAN KUALITAS PELAYANAN PUBLIK PADA KANTOR DESA WERASARI KECAMATAN MALAUSMA KABUPATEN MAJALENGKA - Firman Yudhanegara (Jurnal Ilmu Administrasi CENDEKIA, 2018)
AbstractIn an attempt to provide quality public services, the participation of Village Head is required. The participation of the head of the village in the form of supervision of the implementation of the work of village officials in the framework of the provision of excellent public services achieves the desired objectives. This study uses a combination of qualitative methods, simultaneous triangulation (a balanced combination of quantitative and qualitative). Based on the results of the study, the following are included: 1) the results of the analysis of qualitative data based on the descriptive analysis that Village Head was not able to perform an optimal supervision. This can be seen in the achievement of supervision techniques with the highest average score of 62.30%, with the title